Effect of Bi Substitution on Structural and AC Magnetic Susceptibility Properties of Nd1−xBixMnO3 - Nurul Atiqah Azhar (Crystals, 2020)
This study synthesizes the neodymium-based manganites with Bi doping, Nd1−xBixMnO3 (x = 0, 0.25 and 0.50) using the solid-state reaction route. The crystal structural, morphological and magnetic properties were determined using X-ray diffraction (XRD), fourier transform infrared spectroscopy (FTIR), field emission scanning electron microscopy (FESEM) and AC magnetic susceptibility. The Rietveld refinement confirmed that the compounds were in the single-phase orthorhombic structure of the NdMnO3 with Pbnm space group and lattice parameter b increased with doping from 5.5571 (x = 0) to 5.6787 (x = 0.5). FTIR spectra showed that absorption bands were located within the range of 550–600 cm−1, which corresponded to the Mn–O stretching vibration. FESEM exhibited homogenous compound. The AC magnetic susceptibility measurement studies showed a strong antiferromagnetic (AFM) to paramagnetic (PM) transition existed at 76 K, 77 K and 67 K for samples (x = 0, 0.25 and 0.50), respectively.